Research and application of real time video monitoring system based on IoT and 4G wireless VPDN technology - Zheng DONG; Ying ZHU; Chunze YANG (Dianxin kexue)
For achieving the requirement of real-time video monitoring which is located in the circuit cut-over operating point of the substation of the National Grid Nanjing Branch,China Telecom Nanjing Branch developed a new real-time video monitoring system which was based on internet of things technology and 4G wireless transmission network,by creating a smart pipeline based on 4G VPDN (virtual private dial-up network).The new system has solved the problem that the cable can not be used due to the frequent changing of the circuit cut-over operating points of the substation.